1998
DOI: 10.1002/(sici)1520-667x(1998)10:3<249::aid-mcs2>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized evaporative light scattering detector for application with packed microcolumn high-performance liquid chromatography

Abstract: A miniaturized evaporative light scattering detector (ELSD) compatible with packed microcolumn high‐performance liquid chromatography (HPLC) has been developed. In such a detector, it is particularly important that an efficient nebulization of the column effluent is achieved. Therefore, the geometry of the nebulizer has been optimized. Detector performance was demonstrated for acetonitrile–acetone at 5–100 μL min−1 as mobile phase, a packed microcolumn, 0.7 mm i.d. was used. Isocratic and gradient elutions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Thus, the use of a nebulizer optimized for micro and capillary LC gives a linear dependence between the peak area and the sample mass [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of a nebulizer optimized for micro and capillary LC gives a linear dependence between the peak area and the sample mass [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…9 Greibrokk also demonstrated an interface of microcolumn supercritical fluid chromatography (SFC) to ELSD. 10 A miniaturized ELSD for application with packed microcolumn HPLC or SFC was reported by Andersson et al 11 They found that a makeup solvent (hexane at 30 μL/min) assisted in proper effluent nebulization, while the flow rate of the mobile phase was 5−100 μL/min, too great for CLC or pCEC. Recently, Gaudin et al adapted a commercial detector to micro and CLC, based on the predicted size of the nebulized droplets via the Nukiyama and Tanasawa empirical equation.…”
mentioning
confidence: 99%
“…Then nebulization can be performed efficiently at a relatively low volumetric gas flow rate. 11 Likewise, the lower the mobile phase flow rate, the smaller must be the annular gap of the nebulizer nozzle to accommodate the low level flow rate of the mobile phase. It is reported that design and operation of the nebulizer significantly affect size distribution of resultant aerosols and thus instrument performance, 10,19 hereby the new design structurally concerns about decreasing the parameter δ.…”
mentioning
confidence: 99%